1984
DOI: 10.1073/pnas.81.5.1389
|View full text |Cite
|
Sign up to set email alerts
|

beta-endorphin-(1-27) is an antagonist of beta-endorphin analgesia.

Abstract: ABSTRACT3,-Endorphin-(1-27), a naturally occurring fragment of human f-endorphin (ph-endorphin), diminishes the analgesic effect of ph-endorphin when coinjected intracerebroventricularly into mice. A parallel shift in the doseresponse curve of 3h-endorphin in the presence of (3h-endorphin-(1-27) suggests competition at the same site. The potency of ,,-endorphin-(1-27) in antagonizing analgesia is >4 times greater than that of the opiate antagonist naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 16 publications
2
28
1
Order By: Relevance
“…The increase of the [ 35 S]guanosine-5Ј-O-(3-thio)triphosphate binding stimulated by ␤-endorphin is attenuated by both -opioid receptor antagonist ␤-funaltrexamine and ␤-endorphin(1-27), indicating that ␤-endorphin stimulates bothand putative ⑀-opioid receptors. ␤-Endorphin(1-27) at high doses produces antinociception with the tail-flick test, which is much less potent and has a much shorter duration of action than that produced by ␤-endorphin (Hammonds et al, 1984). We found in the present study that ␤-endorphin(1-27) at 2 nmol given i.c.v.…”
Section: Enhancement Of Formalin-nocifensive Response Bysupporting
confidence: 53%
See 1 more Smart Citation
“…The increase of the [ 35 S]guanosine-5Ј-O-(3-thio)triphosphate binding stimulated by ␤-endorphin is attenuated by both -opioid receptor antagonist ␤-funaltrexamine and ␤-endorphin(1-27), indicating that ␤-endorphin stimulates bothand putative ⑀-opioid receptors. ␤-Endorphin(1-27) at high doses produces antinociception with the tail-flick test, which is much less potent and has a much shorter duration of action than that produced by ␤-endorphin (Hammonds et al, 1984). We found in the present study that ␤-endorphin(1-27) at 2 nmol given i.c.v.…”
Section: Enhancement Of Formalin-nocifensive Response Bysupporting
confidence: 53%
“…␤-Endorphin(1-27) has been demonstrated to be an antagonist and blocks the antinociception induced by ␤-endorphin (Tseng, 2001). This is evidenced by the findings that intracerebroventricular coadministration of ␤-endorphin(1-27) with ␤-endorphin effectively attenuates the ␤-endorphin-induced tail-flick inhibition in mice (Hammonds et al, 1984;Suh et al, 1988;Tseng, 2001). In rats, cointracerebral administration of ␤-endorphin(1-27) with ␤-endorphin microinjected into periaqueductal gray (PAG), raphe obscurus nucleus, posterior nucleus accumbens, medial preoptic area, or acuate hypothalamic nucleus effectively attenuates the tailflick inhibition induced by ␤-endorphin (Tseng and Tang, 1990;Tseng, 2001).…”
Section: Enhancement Of Formalin-nocifensive Response Bymentioning
confidence: 58%
“…Our results, taken together with the studies of Goldstein and his colleague on dynorphin binding sites (Chavkin & Goldstein 1981), suggested that opiate receptors interact with complementary opioid peptides, β-endorphin acting preferentially at a 'β-endorphin receptor' (possibly the ε receptor present in rat vas deferens (Hammonds et al 1984) or the μ receptor in guinea pig ileum (Paterson et al 1983)), dynorphin at a 'dynorphin receptor' (the κ receptor (Chavkin & Goldstein 1981)) and enkephalin at an 'enkephalin receptor' (the δ receptor present in mouse vas deferens (Wuster et al 1979)). The hypothesis proposed that each functional opioid peptide is targetted at a corresponding receptor, ensuring that opiate activity is focused at the site where the appropriate receptor is situated.…”
Section: T19 Thematic Reviewmentioning
confidence: 96%
“…For example, the endogenous cannabinoid receptor ligand anandamide is a partial agonist in rat brain (Mackie et al, 1993;Childers et aI., 1994). Moreover, it has been reported that the opioid peptide ß-endorphin 1_27 may act as an agonist (McKnight et al, 1983), an antagonist (Hammonds et al, 1984;Nicholas and Li, 1985;Suh et al, 1987;Bals-Kubik et al, 1988), or a lowefficacy partial agonist at ‚u-and 8-opioid receptors (Hong et al, 1993) in various experimental paradigms. This is unlike ß-endorphin1.31, which has been found to act as a full agonist at ‚u receptors, and a full-or high-efficacy partial agonist at 6-opioid receptors (Law et al, 1983;Selley and Bidlack, 1992).…”
Section: Discussionmentioning
confidence: 99%